Dissolution and oriented aggregation: transformation from lepidorocite to goethite by the catalysis of aqueous Fe(ii). Issue 129 (15th December 2015) - Yan, Wenjing; Liu, Hui; Chen, Rufen; Xie, Juan; Wei, Yu
Abstract : At a low temperature, lepidocrocite-to-goethite transformation occurred in the presence of Fe(ii ) ions, whereas lepidocrocite was stable in the absence of Fe(ii ) ions. Abstract : At a low temperature, lepidocrocite-to-goethite transformation occurred in the presence of Fe(ii ) ions, whereas lepidocrocite was stable in the absence of Fe(ii ) ions. The results reveal that Fe(ii ) accelerates the dissolution of the lepidocrocite. The dissolved Fe(iii ) ions hydrolysed to form goethite. The mechanism of transformation included dissolution-reprecipitation and oriented aggregation.